CD14 Is Expressed and Released as Soluble CD14 by Human Intestinal Epithelial Cells In Vitro: Lipopolysaccharide Activation of Epithelial Cells Revisited - Funda, David P. (American Society for Microbiology, 2001)
Human endothelial as well as epithelial cells were shown to respond to lipopolysaccharides (LPSs). However, the expression and release of CD14 by these so-called CD14-negative cells have not been studied in detail. We investigated three human intestinal epithelial cell lines (ECLs), SW-480, HT-29, and Caco-2, for their expression of CD14 and CD11c/CD18 as well as their responsiveness to endotoxins. Fluorescence-activated cell sorter analysis revealed no expression of CD11c/CD18, but there was low expression of membrane-bound CD14 on HT-29, Caco-2, and SW-480 ECLs. Both Western blotting and reverse transcription-PCR confirmed the CD14 positivity of all three intestinal ECLs. No substantial modulation of CD14 expression was achieved after 6, 8, 18, 24, and 48 h of cultivation with 10-fold serial dilutions of LPS ranging from 0.01 ng/ml to 100 μg/ml. Interestingly, soluble CD14 was found in the tissue culture supernatants of all three ECLs. Finally, only HT-29 and SW-480, and not Caco-2, cells responded to LPS exposure (range, 0.01 ng/ml to 100 μg/ml) by interleukin 8 release. Thus, we show that HT-29, SW-480, and Caco-2 human intestinal ECLs express membrane-bound CD14. As Caco-2 cells did not respond to LPS, these cell lines might be an interesting model for studying the receptor complex for LPS. The fact that human intestinal epithelial cells are capable not only of expression but also of release of soluble CD14 may have important implications in vivo, e.g., in shaping the interaction between the mucosal immune system and bacteria in the gut and/or in the pathogenesis of endotoxin shock.